Family planning decision-making in relation to psychiatric disorders in women: a qualitative focus group study - Shahenda A. I. H. Ahmad; Jorina Holtrop; Monique J. M. van den Eijnden; Nini H. Jonkman; Maria G. van Pampus; Odile A. van den Heuvel; Birit F. P. Broekman; Noralie N. Schonewille (BMC, 2024)
Abstract Background Recent studies revealed an elevated likelihood of unintended pregnancies among women with psychiatric disorders compared to their counterparts without such vulnerability. Despite the importance of understanding family planning decision-making in this group, qualitative inquiries are lacking. This study explored family planning decisions among women with psychiatric disorders. Methods Utilizing a qualitative approach, three focus group discussions were conducted with purposive sampling: women with a history of unintended pregnancies (N = 3), women without children (N = 5), and women with a history of intended pregnancies (N = 9), all of whom had self-reported psychiatric disorders. Using thematic framework analysis, we investigated the themes "Shadow of the past," reflecting past experiences, and "Shadow of the future," reflecting future imaginaries, building upon the existing "Narrative Framework." Results The Narrative Framework formed the foundation for understanding family planning among women with psychiatric disorders. The retrospective dimension of focus group discussions provided opportunities for reflective narratives on sensitive topics, revealing emotions of regret, grief and relief. Childhood trauma, adverse events, and inadequate parenting enriched the "Shadow of the past". The "Shadow of the present" was identified as a novel theme, addressing awareness of psychiatric disorders and emotions toward psychiatric stability. Social influences, stigma, and concerns about transmitting psychiatric disorders shaped future imaginaries in the shadow of the future. Conclusions This study enlightens how family planning decision-making in women with psychiatric disorders might be complex, as marked by the enduring impact of past experiences and societal influences in this sample. These nuanced insights underscore the necessity for tailored support for women with psychiatric disorders.